Abandoned on the wild frontier - Jackson, Dave.; Jackson, Neta.; Jackson, Julian (Minneapolis : Bethany House Pub., 1995)
Gilbert Hamilton is left alone on the frontier when his father is killed and his mother is kidnapped by Sauk Indians during the War of 1812. Haunted by memories of his mother, Gil attends a camp meeting led by Peter Cartwright, a Methodist circuit-rider evangelist. Cartwright allows the boy to move with his family to Illinois, where Gil can begin the search for his mother.
Keywords: Orphans -- Fiction; Frontier and pioneer life -- Fiction; Christian life -- Fiction; Evangelists -- Fiction; Orphans -- Fiction; Frontier and pioneer life -- Fiction; Christian life -- Fiction; Evangelists -- Fiction